Post-embryonic organogenesis and plant regeneration from tissues: two sides of the same coin? - Perianez-Rodriguez, Juan; Manzano, Concepcion; Moreno-Risueno, Miguel A. (Frontiers in Plant Science, 2014)
Plants have extraordinary developmental plasticity as they continuously form organs during postembryonic development. In addition they may regenerate organs upon in vitro hormonal induction. Advances in the field of plant regeneration show that the first steps of de novo organogenesis through in vitro culture in hormone containing media (via formation of a proliferating mass of cells or callus) require root postembryonic developmental programs as well as regulators of auxin and cytokinin signaling pathways. We review how hormonal regulation is delivered during lateral root initiation and callus formation. Implications in reprograming, cell fate and pluripotency acquisition are discussed. Finally, we analyze the function of cell-cycle regulators and connections with epigenetic regulation. Future work dissecting plant organogenesis driven by both endogenous and exogenous cues (upon hormonal induction) may reveal new paradigms of common regulation.